Resurrection of the name Pachycheta Portschinsky for a genus of Tachinidae (Diptera) - O’hara, James E. (Zootaxa, 2009)
While verifying names in the original literature for a forthcoming catalogue, I discovered a senior objective synonym for the genus currently recognized as Barychaeta Bezzi, 1906. As will be explained below, the generic name Pachycheta Portschinsky, 1881 has priority over Barychaeta. The unjustified emendation Pachychaeta is dated from Brauer and Bergenstamm (1891) instead of Bezzi (1906) as cited in Neave (1940). The correct spelling of the type species of Pachycheta is discussed. The genus Pachycheta was described by Portschinsky (1881: 278) with a single included species, Pachycheta jaroschewsky Portschinsky, 1881 (type species by monotypy). The generic name appeared next in Brauer and Bergenstamm (1891: 99 [also 1892: 403]), where it was cited in a systematic list with the spelling Pachychaeta. The Code (ICZN 1999, Article 33) is very specific about the difference between an emendation (which is an available name) and an incorrect subsequent spelling (which is not an available name), and according to the criteria therein Pachychaeta in Brauer and Bergenstamm (1891) is the former. An emendation is “any demonstrably intentional change in the original spelling of a name other than a mandatory change” (Article 33.2), and can be inferred “when two or more names in the same work are treated in a similar way” (Article 33.2.1). Brauer and Bergenstamm (1891) frequently used emended spellings of taxa in favor of original spellings, for instance changing the original ending of names from -cheta to -chaeta (e.g., Gymnocheta to Gymnochaeta, Pericheta to Perichaeta) and from -mya to -myia (e.g., Acemya to Acemyia, Ceromya to Ceromyia), thereby fulfilling the requirement of Article 33.2.1. Such emendations are now considered unjustified under Article 33.2.3. Therefore, Pachychaeta is an unjustified emendation and a junior objective synonym of Pachycheta Portschinsky and takes authorship and date from Brauer and Bergenstamm (1891). Neave (1940: 507) credited Bezzi (1906) with the emended name, but Brauer and Bergenstamm (1891) were the first to satisfy the conditions of an unjustified emendation as set forth in the present Code (ICZN 1999).